PUSAT FASHION PONTIANAK - Mauluddin, Asep; Khaliesh, Hamdil; Irwin, Irwin (JMARS: Jurnal Mosaik Arsitektur, 2021)
West Kalimantan has a wide variety of cultures, ethnicities, and religions so that it has distinctive fashion products in each region such as cloth, songket, and also very varied weaving. The number of retail fashion also affects the interest and attractiveness of the community towards the development of fashion in Pontianak. Fashion is growing rapidly at this time due to technological developments where young people attach importance to fashion to support their appearance. Therefore, we need a fashion center in Pontianak that can be used to introduce, produce, market and most importantly promote West Kalimantan regional fashion. This building design uses a method that compares the results of observations with literature studies, comparative studies and standards applicable to fashion buildings and facilities, then analyzes the expected internal and external aspects. The design of the Pontianak Fashion Center building will be integrated with the surrounding area, and also the concept of the shape of the building which is applied from traditional clothing so that it can become a new icon of the city of Pontianak.